Testing the Random Walk: The Case of Hong Kong Stock Exchange - Chaibi, Latifa Fatnassi (Journal of Empirical Studies, 2014)
The purpose of this paper is to investigate random walk in HongKong stock exchange. The unit root, autocorrelation and the variance ratio tests are applied, using daily data on returns of two indexes in the period 1997:7 to 2012:12. For two indexes, the null hypothesis of random walk is rejected and therefore the markets are no weak-form efficiency.